ANALISIS PEMBELAJARAN BERDIFERENSIASI UNTUK MENGEMBANGKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI PADA MATA PELAJARAN IPAS KELAS V SDN KUBANG SEPAT 1 - Pinanggih, Adlin Putri; Syachruroji, Ahmad; Cipta, Nana Hendra (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2025)
This study aims to describe the planning, implementation, and results of differentiated learning in the IPAS subject on higher-order thinking skills of fifth-grade students at SDN Kubang Sepat 1, Cilegon. The research employed a qualitative approach, with data collected through observation, interviews, and documentation. Data analysis was conducted using the interactive analysis model of Miles and Huberman. The results show that differentiated learning planning at SDN Kubang Sepat 1 was carried out thoroughly, particularly in Grade V for the IPAS subject. The implementation of differentiated learning in IPAS lessons has been well-executed. The learning activities followed the teaching module closely and highlighted key elements of differentiation: content differentiation, process differentiation, product differentiation, and learning environment. Throughout the learning process, instructional tools were consistently used and optimized, and students actively participated in all learning activities. In terms of learning outcomes, SDN Kubang Sepat 1 regularly conducted evaluations, both written and non-written, and the results indicated that the students’ higher-order thinking skills in Grade V have begun to show development.